The Ex-Dividend Day Anomaly in the Spanish Stock Market - Garcia-Blandon, Josep; Martinez-Blasco, Monica (Pontificia Universidad Católica del Perú. CENTRUM, 2012)
The purpose of this paper was to investigate the behavior of stock returns and trading volumes around ex-dividend dates in the Spanish stock market, using event study methodology. Clear consensus is evident in the literature about the fact that stock prices fall by less than the dividend paid on ex-dividend days. This behavior indicates a preference for capital gains over dividends, generally explained in terms of tax advantages. Contrary to the existing consensus, the results of this study did not reflect significant abnormal returns on ex-dividend days. The finding is consistent with the fact that nowadays Spain taxes dividends and capital gains at the same rate. In addition, abnormally high trading volumes are apparent around ex-dividend dates, especially for high-yield stocks.
Keywords: Ex-dividend days; Abnormal returns; Abnormal volumes; Event studies; https://purl.org/pe-repo/ocde/ford#5.02.04